Market research on the energy sector-s shift to a sustainable electrical path - Morgado, Afonso Maria Baptista Rebelo De Sousa (2022)
The 46 Gt greenhouse gas emissions is starting to be felt at a global level, driving Earth to a burning platform. Therefore, an electrical transition of the energy sector generated through alternative sources represents a reliable solution to reverse this situation. Which combined with the adoption of behavioural changes could result in a decrease of 20 Gt. Having had the opportunity to focus on the behavioural changes, they have proved to be a necessary solution that will be triggered through the right government's policies to be adopted by both individuals and enterprises.